The new Pacific community in the 1990s - Hyun, Seung Jong.; Kim, Young Jeh (New York : M.E. Sharpe, 1996)
"The Center for Asia Pacific Studies was organized by Kon-Kik University, Seoul, Korea and Pacific States University."
Keywords: Pacific Area